Inappropriate medication prescribing, polypharmacy, potential drug-drug interactions and medication regimen complexity in older adults attending three referral hospitals in Asmara, Eritrea: a cross-sectional study - Nuru Abdu; Saleh Idrisnur; Hanae Said; Lude Kifle; Natnael Habte; Semira Ghirmai; Tomas Tewelde; Senai Mihreteab Siele; Eyasu H. Tesfamariam (BMC Geriatrics)
Abstract Background Older adults often face several chronic illnesses that require them to take multiple medications. The increased number of prescribed medications has led to more complex medication regimens, putting older adults at a higher risk of potential drug-drug interactions, inappropriate medication prescribing, and adverse events. This study aimed to assess inappropriate prescribing practices, polypharmacy, medication regimen complexity, and their determinants in older adults. Methods A cross-sectional study was conducted among older adults (aged 65 years and above) who visited three referral hospitals in Asmara, Eritrea, between June and August, 2023. A stratified random sampling technique was used, and data were collected from patient prescriptions, medical cards, and through interviews with a questionnaire. Inappropriate medication prescribing was evaluated using STOPP (Screening Tool of Older Person's Prescriptions)/ START (Screening Tool to Alert to Right Treatment) criteria version 3. Potential drug-drug interactions (pDDIs) and medication regimen complexity (MRC) were assessed using Lexi-comp drug interaction checker and MRC index, respectively. Descriptive statistics, logistic regression, Pearson’s correlation coefficient, independent samples t-test, one-way Analysis of Variance, and paired t-test were employed using IBM SPSS (version-26.0). Results A total of 430 respondents, with a similar male to female ratio, were included. The prevalence of polypharmacy was 5.3% (95%CI: 3.2, 7.5). Moreover, the prevalence of clinically significant pDDI was 51% (95%CI: 46, 56). The most common medicines involved in clinically significant pDDIs were enalapril (n = 179) and acetylsalicylic acid (n = 124). The presence of chronic illness (AOR = 7.58, 95%CI: 3.73, 15.39) and the number of drugs prescribed (AOR = 2.80, 95%CI: 1.91, 4.10) were predictors of clinically significant pDDIs. The prevalence of potentially inappropriate medications (PIMs) and potential prescribing omissions (PPOs) were 27.4% (95% CI: 23.4, 31.8) and 13.3% (95% CI: 10.3, 16.7), respectively. The most common PIMs were long-acting sulfonylureas (n = 63) and aldosterone antagonists (n = 19). Besides, proton pump inhibitors (PPIs) (n = 41) and cardio-selective beta-blockers (n = 14) were the most common PPOs identified. Age (AOR: 0.95, 95% CI: 0.92, 0.98), presence of chronic illness (AOR: 1.51, 95% CI: 0.81, 2.80), and number of drugs prescribed (AOR: 2.01, 95% CI: 1.51, 2.69) were significant factors associated with PIM. MRCI score was a significant determinant of PPO (AOR: 1.25, 95% CI: 1.14, 1.38). The mean (SD) of the overall MRCI score was 9.1 (3.7), with dose frequency being the major contributor. The number of drugs prescribed was a determinant of MRCI score (r = 0.625, p < 0.001). Conclusion Inappropriate medication prescribing and clinically significant drug-drug interactions were common among older adults, highlighting the need for immediate attention from policymakers, program managers, and healthcare professionals.